Biotechnological Processes Simulating the Natural Fermentation Process of Bee Bread and Therapeutic Properties—An Overview - Barta, Daniel Gabriel; Cornea-Cipcigan, Mihaiela; Margaoan, Rodica; Vodnar, Dan Cristian (Frontiers in Nutrition, 2022)
Recent signs of progress in functional foods and nutraceuticals highlighted the favorable impact of bioactive molecules on human health and longevity. As an outcome of the fermentation process, an increasing interest is developed in bee products. Bee bread (BB) is a different product intended for humans and bees, resulting from bee pollen's lactic fermentation in the honeycombs, abundant in polyphenols, nutrients (vitamins and proteins), fatty acids, and minerals. BB conservation is correlated to bacteria metabolites, mainly created by Pseudomonas spp., Lactobacillus spp., and Saccharomyces spp., which give lactic acid bacteria the ability to outperform other microbial groups. Because of enzymatic transformations, the fermentation process increases the content of new compounds. After the fermentation process is finalized, the meaningful content of lactic acid and several metabolites prevent the damage caused by various pathogens that could influence the quality of BB. Over the last few years, there has been an increase in bee pollen fermentation processes to unconventional dietary and functional supplements. The use of the chosen starters improves the bioavailability and digestibility of bioactive substances naturally found in bee pollen. As a consequence of enzymatic changes, the fermentation process enhances BB components and preserves them against loss of characteristics. In this aspect, the present review describes the current biotechnological advancements in the development of BB rich in beneficial components derived from bee pollen fermentation and its use as a food supplement and probiotic product with increased shelf life and multiple health benefits.